A morphometric analysis of Thrips tabaci Lindeman species complex (Thysanoptera: Thripidae). (January 2023) - Musa, Saranda; Ladányi, Márta; Loredo Varela, Roberto Carlos; Fail, József
Abstract: The onion thrips, Thrips tabaci Lindeman, is a cryptic species complex of three distinct lineages: L1, L2, and T, which exhibit considerable variation in their biological and ecological traits. The most accurate method for their identification is based on molecular techniques. This study aimed to investigate the morphometric variation of T. tabaci cryptic species complex and to distinguish characters that may be useful in discriminating the lineages. For this purpose, morphometric measurements were performed on the eggs, newly hatched first instar larvae, and newly emerged adults. Our results revealed significant differences in egg size between the three lineages. Moreover, the PCA analysis conducted on morphometric measurements of the first instar larvae and adults showed that females of the T lineage are very well separated from the females of the L lineages in the adult stage but not in the first instar larval stage. The distinction between the females is partially congruent with the results of genetic studies. Moreover, our results indicate that adult sexual dimorphism with regard to size in L1 and T lineages is not mediated by the size of eggs and first instar larvae, and this may be due to the different growth rates of males and females. Graphical abstract: Image 1 Highlights: Morphometric measurements are used to discriminate between lineages of Thrips tabaci . Egg size is different between lineages of Thrips tabaci . Females of the L and T lineages are morphologically different from each other in the adult but not in the first instar larval stage. Sexual size dimorphism in L1 and T lineages is not present in eggs and first instar larvae but develops by adult emergence.